Ametor A. Semenov, 1900 (Coleoptera: Hydrophilidae) – a new genus of beetles for the fauna of Kazakhstan - I.I. Temreshev (Кавказский энтомологический бюллетень, 2012)
А new genus and species Ametor rudesculptus Semenov, 1900 is recorded for the fauna of Kazakhstan